2022
DOI: 10.1186/s12905-022-01810-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive leadership in clinical encounters with women living with HIV

Abstract: Background Women living with HIV (WLWH) report low engagement in health care, missed office visits, and less engagement in the clinical encounter. Strengthening the clinical encounter for WLWH may improve health outcomes and quality of life. The Adaptive Leadership Framework for Chronic Illness offers specific adaptive leadership strategies for providers to improve patient-provider interactions. The purpose of this study was to examine adaptive leadership behaviors that contribute to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Not all of the studies described using a theoretical framework, but those that did use the transtheoretical model for change, 33 intersectional theoretical framework, 36 the National Academy of Medicine's quality of care aims, 35 and the Adaptive Leadership Framework for Chronic Illness. 34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Not all of the studies described using a theoretical framework, but those that did use the transtheoretical model for change, 33 intersectional theoretical framework, 36 the National Academy of Medicine's quality of care aims, 35 and the Adaptive Leadership Framework for Chronic Illness. 34 …”
Section: Resultsmentioning
confidence: 99%
“…The participants ranged in age from 21 to 69 and the average age across studies ranged from 42 to 57. 18 , 26 36 Not all studies reported on the socioeconomic status of participants, but those that did described a large proportion of participants as having less than a 4-year college degree with many being low income or living below the poverty line. 26 , 27 , 29 , 31 , 32 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on factors hindering or facilitating ART adherence and viral suppression among Black women suggests that poor health care provider relationships (perceived stigma, discrimination) and lack of available providers are associated with suboptimal ART adherence (Rice et al, 2020). Alternatively, Randolph et al (2022), in a study exploring clinical encounters of women with HIV, found that providers who are perceived as supportive were trusted, communication was valued, and trust building takes time.…”
Section: Discussionmentioning
confidence: 99%